Implementation of E-Commerce and Web-Based Company Profile on CV. Andromeda Multi Sarana - Sry Dhina Pohan; Mohammad Hilmi Mubarok (FKOM UNIKU, 2022)
CV.Andromeda Multi Sarana (AMS) is a company engaged in swallow consultants that provides solutions for farmers in conventional and modern cultivation in selling wallet business products. The wide sales area for wallet products proves that AMS is successful in marketing wallet products. At AMS, purchase data and wallet product data are processed manually, making it difficult to process large amounts of data and reporting is not integrated to the AMS leadership. The E-commerce system and company profile on AMS are made web-based using the prototype system development method which is useful in facilitating the process of completing the stages of making the system and according to the wishes of the user. The E-commerce system and company profile on AMS produce an integrated system capable of processing large amounts of data and a website that functions to expand AMS' market share with a company profile that explains the purpose of AMS.